Spatial distribution of nests of Nasutitermes sp (Isoptera : Termitidae) in a Cerrado area in southeastern Brazil - Buschini, MLT (Entomological Soc Amer, 1999)
The density and aggregation patterns of nests of a species of Nasutitermes were determined in an area of 12,750 m(2). We found 131 nests in this area, and the distribution pattern was regular, with a density equaling 102.74 nests per hectare. Nest volume was determined from the height and diameter of 105 nests and varied from 1.59 to 192.46 dm(3). of the colonies, 70.5% had a volume below the mean value: 51.4% of these had volumes lower than 9 dm(3). Regression between the mean volumes and the distance of the 2 nearest nests was positive and significant (P < 0.001), suggesting competition between colonies.
Keywords: Nasutitermes; spatial distribution; temites; Brazil